A remarkable age-related increase in SIRT1 protein expression against oxidative stress in elderly: SIRT1 gene variants and longevity in human. - Ulkan Kilic; Ozlem Gok; Ufuk Erenberk; Mehmet Rusen Dundaroz; Emel Torun; Yasar Kucukardali; Birsen Elibol-Can; Omer Uysal; Tolga Dundar (PLoS ONE, 2015)
Aging is defined as the accumulation of progressive organ dysfunction. Controlling the rate of aging by clarifying the complex pathways has a significant clinical importance. Nowadays, sirtuins have become famous molecules for slowing aging and decreasing age-related disorders. In the present study, we analyzed the SIRT1 gene polymorphisms (rs7895833 A>G, rs7069102 C>G and rs2273773 C>T) and its relation with levels of SIRT1, eNOS, PON-1, cholesterol, TAS, TOS, and OSI to demonstrate the association between genetic variation in SIRT1 and phenotype at different ages in humans. We observed a significant increase in the SIRT1 level in older people and found a significant positive correlation between SIRT1 level and age in the overall studied population. The oldest people carrying AG genotypes for rs7895833 have the highest SIRT1 level suggesting an association between rs7895833 SNP and lifespan longevity. Older people have lower PON-1 levels than those of adults and children which may explain the high levels of SIRT1 protein as a compensatory mechanism for oxidative stress in the elderly. The eNOS protein level was significantly decreased in older people as compared to adults. There was no significant difference in the eNOS level between older people and children. The current study is the first to demonstrate age-related changes in SIRT1 levels in humans and it is important for a much better molecular understanding of the role of the longevity gene SIRT1 and its protein product in aging. It is also the first study presenting the association between SIRT1 expression in older people and rs7895833 in SIRT1 gene.